La depresión como consecuencia del sobrepeso en estudiantes de Bachillerato del Colegio Adolfo Valarezo de la ciudad de Loja. - Espinosa Maldonado, Willan Sebastián (2017)
Depression caused by overweight is one of the most common disorders that can be evidenced in society, these individuals usually do not have the courage to perform any activity, be it physical or social and are usually confined within their homes, so eating Can be an automatic activity that fill part of that time, to which we can deduce that depression as well as being a consequence of being overweight can also be identified as a cause of it. The present investigation determined whether depression is a consequence of being overweight in the high school students of the school Adolfo Valarezo of the city of Loja, for which a descriptive, prospective and transversal study was carried out to 430 students belonging to the baccalaureate section, where Applied instruments for the measurement of weight and height for the calculation of the body mass index, which allowed to evidence the existence of 73 students diagnosed with overweight, and the CES-DR scale of the Center of Epidemiological Studies was applied for the verification of depressive degrees ; It was determined that: 79.4% of students had depression, of which 71.2% confirmed the presence of mild-moderate depression and 8.2% referred to major depression. In addition, this scale made it possible to determine the main causes of depression in overweight adolescents, which were reflected in the items: I had lost interest in my daily activities, people were unfriendly, I felt sad, I had trouble sleeping and I felt tired all the time. It was also found that the female gender represents greater compatibility with the depressive symptomatology, with 53.4% of the students. Finally, it was verified that there is a direct relationship between depression and overweight, resulting in a positive result to the objectives that the following investigation was proposed. Key words: Depression, Overweight, CES-D-R scale, adolescents.